Football Results and Stock Market Returns:A Multi-Country Event Study. - Lee, Kien Lin (2011)
This paper considers the impact of match results on the stock returns of nine professional football clubs. Each of the nine clubs was selected as a representative for the nine countries (England, Scotland, Italy, Germany, Netherlands, Portugal, Turkey, France and Denmark). The teams played 278 domestic matches in total, across the time span of one season in the respective country’s tier-1 football division. The event study found that the market response is significant and positive in the context of victories and negative for draws and defeat across careful examination on the nine public listed teams in the sample. Unexpected results do not have a significant influence on stock returns in overall and the home ground advantage has also proven to be insufficient in explaining investors’ reaction in the stock market following each of the possible game outcomes i.e. Win, Draw or Loss.